Medical interventions to reverse pulmonary hypoplasia in the animal model of congenital diaphragmatic hernia: A systematic review. Issue 8 (20th May 2015) - Eastwood, Mary Patrice; Russo, Francesca Maria; Toelen, Jaan; Deprest, Jan
Summary Objective We aimed to systematically review all published pre‐clinical research on prenatal medical treatment of pulmonary hypoplasia in congenital diaphragmatic hernia (CDH). Background The neonatal mortality due to isolated CDH remains high. Whether fetal endoscopic tracheal occlusion (FETO) reduces mortality is still to be demonstrated. Therefore more potent preferentially medical therapy would be welcomed. Methods We searched MEDLINE (Pubmed), Embase and the Web of Science including all studies from the earliest date (1951) to December 2013. Article quality was assessed using the modified CAMRADES checklist. Inclusion criteria were those animal studies addressing prenatal medical interventions and principal variables were confirmation of a diaphragmatic defect, lung to body weight ratio (LBWR), formal airway morphometry or DNA/protein content. Results In total 983 articles were identified. Following abstract review, 96 articles were assessed by two authors in agreement with a third for eligibility. Of these, 43 were included in the final analysis. The median number of study quality checklist items (maximum 10) scored was 4 (IQ range: 2–5). Thirty (69.8%) of studies were in the nitrofen rat. The majority were treated with vitamins or glucocorticoids. Single studies reported some improvement in lung morphology with alternative therapies. It was impossible to identify a pattern in animal model selection or creation, mode, time point or duration of treatment and readouts. Only one study reported a sample size calculation. Conclusion Comparison in pre‐clinical studies in CDH is challenging due to methodological variation. Agreed standardized methods need to be applied in future investigation of new medical therapies. Pediatr Pulmonol. 2015; 50:820–838. © 2015 Wiley Periodicals, Inc.